Shahnaz Majid lwn Dato' Sri Mahmud Abu Bekir Taib [2018] 6 CLJ 663 - Sufeena, Nur Atheefa (Kanun: Jurnal Undang-undang Malaysia; Vol 31 No 1 (2019): Kanun: Jurnal Undang-undang Malaysia Volume 31 Number 1 January 2019, 2019)
-